Brief Christian histories : getting a sense of our long story - White, James W. (James Wildon); McLaren, Brian D., 1956-; Addington, Melissa White (Eugene, Oregon : Wipf & Stock, 2014)
How do we undergird Christian enthusiasm with Christian substance? Brief Christian Histories combines biblical and ecclesial history in a single volume, taking readers through 4000 years of our religion's history using four themes of interest: WHO has led us? HOW have we been guided ethically? WHAT have been our faith practices and pieties? WHERE have we interacted with culture, and to what effect? Reading any one chapter will give readers a feel for the Christian narrative as a whole. Reading two or more narratives will broaden readers' understanding of where we have come from-all to help understand this big religion of ours, deepen ourselves in it, and keep our faith fresh and moving forward. We move for God's New Order (basileia)-about which Jesus taught, for which he taught us to pray, and into which he invites our enthusiastic, substantive sojourning.
Includes bibliographical references (pages 215-218) and indexes.
Print version record.
Keywords: Christianity; Church history -- Popular works; Christianity; Church history; RELIGION / Christian Church / History; RELIGION / Christianity / History; Popular works; Electronic books